The Selfie Syndrome Phenomenon and its Implications for Mental Health - Rahma Mulyani, Rila; Husnul Hayati, Ridha (Universitas Negeri Padang, 2024)
The phenomenon of selfie syndrome is a term that refers to the widespread tendency among individuals to take and share excessive photos of themselves via social media and has become an inseparable part of digital culture. This research presents an in-depth literature study of the selfie syndrome phenomenon and its implications for individual mental health. Through an analysis of a number of relevant empirical and theoretical studies, this article explores the factors that influence the tendency to take excessive selfies, such as social motivation, self-esteem, and the need for self-validation. In addition, the implications of the Selfie Syndrome phenomenon for mental health are studied in detail, including its impact on low self-esteem, disturbed body image, and the risk of social media addiction. This literature study also discusses prevention and intervention strategies that can be applied in non-formal education and clinical practice to overcome the negative impacts of the selfie syndrome phenomenon. By summarizing key findings from the existing literature, this article helps educators and mental health professionals understand the difficulties individuals face in navigating the increasingly popular selfie culture.Keywords:Selfie Syndrome, Mental Health, Social Media.